An introduction to the diagnosis of plan disease - Brathwaite, Chelston W.D. (IICA, 2021)
Plan diseases are undoubtedly one of the major factors which limit the productivity of crops throughout the tropics. In order to control these diseases and so limit their impact on food production, correct diagnosis is important.